Sexualidade de idosas na perspectiva freireana através doscírculos de cultura - Rodrigues, Daysi Mara Murio Ribeiro (2014)
The population ageing, its feminizations and the issues related to the sexuality in this vital phase are realities that makes with promoting the quality of life to be a challenge to be won. The aim of this study was to analyze the educative pathway in the sexuality thematics through the circles of culture along a group of old women. It was treated about field research, using the research-action method, according the Freire´s methodologic referential, permeating the circles of culture while the dynamics spaces of learning and Exchange of knowledge in which the subject get together in the education process to investigate themes of interest of their own group. Through this referential occurred 3 phases: Thematic Investigation; Codification/Decodification and Critical Unveiling. In the study participated 15 old women who matched the exposed selection criteria; be participant of the socialization for ageing group, be 60 years old or more, have mental conditions to answer the interview and participate of the circles of culture. The interviews occurred among the months of April and May of 2014 with average duration of 30 minutes. In the second moment it was achieved the Circle of Culture with average duration of 57 minutes. The data were analyzed by the technician of Contents Analysis pursuant Minayo. It was evidenced that, among the women of this study, there was difficulty in conceptualize the sexuality, and reducing the concept to the sex. There was also a divergence of the sexuality by gender and eventually the sex was configured as a practice of the youth. The women´s need to come loose from the situations-limit found became a catalyst aspect so that the dialog emerged spontaneously, advanced in its critically to each circle of culture achieved, meeting the critical unveiling of the discussed thematics. This way, the old women of this study uncovered, as from the Circles of Culture, the bio psychosocial comprehension of the sexuality, the comprehension of the social and psychological differences of the sexuality and the comprehension of the sexuality on Ageing. The educative practice achieved allowed the dialogicity and conducted to the reflection about the sexuality. This way, the dialogicity, that permeated the debate about the theme sexuality with these women allowed them to burst the ties of the prejudice related to the sexuality in the ageing, as well as built the construction of the blown up concept of the thematic area. The dialog also allowed to reveal the educative actions developed with the application of the liberator methodology, it was able to provide the critical unveiling and the women´s empowering, in order to reach the aim of the liberation.